2001
DOI: 10.1890/0012-9658(2001)082[1007:mcctez]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

MACROALGAL CANOPIES CONTRIBUTE TO EELGRASS (ZOSTERA MARINA) DECLINE IN TEMPERATE ESTUARINE ECOSYSTEMS

Abstract: Loss of eelgrass (Zostera marina) habitat from temperate estuaries worldwide often coincides with increased macroalgal accumulations resulting from increased delivery of anthropogenic nitrogen. We conducted macroalgal enclosure/exclosure experiments during summer 1998 within eelgrass populations in two estuaries of Waquoit Bay, Massachusetts, USA, to evaluate how increased macroalgal biomass affects density, recruitment, growth rate, and production of eelgrass. One estuary featured a low nitrogen loading rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
153
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 323 publications
(164 citation statements)
references
References 52 publications
7
153
4
Order By: Relevance
“…Increasing input of anthropogenic nutrients into coastal areas and resultant blooms of macroalgae (Burkholder et al, 2007;Hauxwell et al, 2001) may lead to seagrass ecosystem degradation. The present study demonstrated the negative effects of adding green algae U. pertusa and inorganic nutrients on Z. marina.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing input of anthropogenic nutrients into coastal areas and resultant blooms of macroalgae (Burkholder et al, 2007;Hauxwell et al, 2001) may lead to seagrass ecosystem degradation. The present study demonstrated the negative effects of adding green algae U. pertusa and inorganic nutrients on Z. marina.…”
Section: Discussionmentioning
confidence: 99%
“…Seagrass decline in temperate estuaries under high nutrient enrichment often coincides with high macroalgae biomass (Burkholder et al, 2007;Hauxwell et al, 2001;Short and Burdick, 1996;Thomsen et al, 2012;Valiela et al, 1997). The negative effects of macroalgal blooms on seagrasses have been documented in many areas of the world, such as Australia, Japan, America and Europe (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Landderived nutrient loading to coastal waters often results in higher nutrient concentrations in estuaries (Nixon 1995;Valiela et al 1997), which stimulate primary production (Nixon 1992;Howarth 1988). This eutrophication of estuarine and coastal waters leads to increases in phytoplankton concentrations (Tomasky et al 1999), and to changes in biomass and species composition of the macroalgal canopies (Lavery et al 1991;Valiela et al 1997;Rafaelli et al 1998;Hauxwell et al 2001). Increased primary production owing to increased nutrient supply can control higher trophic levels in both benthic and pelagic food webs (Rafaelli et al 1998;Ware and Thompson 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Increased primary production owing to increased nutrient supply can control higher trophic levels in both benthic and pelagic food webs (Rafaelli et al 1998;Ware and Thompson 2005). Macroalgal blooms, in particular, have had further consequences, often shading and replacing seagrass meadows (McGlathery 2001;Hauxwell et al 2001), as well as fostering of hypoxic conditions (D'Avanzo and Kremer 1994;Diaz 2001) that decrease abundance of invertebrates (Hauxwell et al 1998;Oesterling and Pihl 2001) and fish (Baden et al 1990;Deegan et al 2002).…”
Section: Introductionmentioning
confidence: 99%